THE EFFECT OF WORK-LIFE BALANCE ON JOB SATISFACTION MEDIATED BY JOB STRESS - Gede Ferry Andrean; Made Surya Putra (Adisam Publisher, 2026)
This study aims to examine and explain the effect of work-life balance on job satisfaction mediated by job stress at Bali Mutia Car Rental. This research adopts a quantitative associative design involving 62 respondents selected through a saturated sampling method. Data collection was conducted using questionnaires, and the analysis was performed using inferential techniques, specifically SEM-PLS (Structural Equation Modeling–Partial Least Squares) with SmartPLS 4.0 software. The findings reveal that work-life balance negatively influences job stress while positively affecting job satisfaction. Furthermore, job stress has a negative impact on job satisfaction and serves as a mediating variable in the relationship between work-life balance and job satisfaction. These results are consistent with role theory, which suggests that imbalances in roles may lead to role conflict, thereby disrupting work-life balance and increasing job stress. Elevated levels of stress, in turn, contribute to a decline in employee job satisfaction. This research is expected to offer practical insights for organizations in enhancing employee job satisfaction by managing work-life balance and job stress effectively.